URANIUM DEPOSITS DATABASE FOR THE PURPOSE OF NUCLEAR FORENSICS IN UKRAINE - Dudar, Tamara; Buhera, Margaryta; Lysychenko, Georgii; Englebrecht, Amy (Proceedings of National Aviation University, 2014)
The problem of illicit trafficking of nuclear materials is reviewed. The IAEA statistical data on nuclearmaterial trafficking for the period from 1993 to 2012 are analyzed. Uranium ores from operating deposits in Ukraineare examined taking into account their attributes and features for the purpose of nuclear forensics.